Lifestyles and non-communicable disease status among primary health care staff in Kuantan, Pahang - Md Aris, Mohd Aznan; Tin, Myo Han; Mohd Shukri, Nor Azwani; Abdullah, Fa’iza (2016)
Unhealthy lifestyle is one of the risks of non-communicable disease (NCDs) in our population even among the healthcare provider. They should be as the role model for their NCDs patients in the clinics. Therefore, this study was to determine the lifestyle practices and lifestyle-related NCDs (LR-NCDs) status was to determine the lifestyle practice and lifestyle-related NCDs (LR-NCDs) status among primary health care staffs.